Foundations of cognitive grammar - Langacker, Ronald W. (Stanford University Press, 1987)
In contrast to current orthodoxy, the author of this work argues that grammar is not autonomous with respect to semantics, but rather reduces to patterns for the structuring and symbolization of conceptual content.